The Equality Effects of the 'Hyper‐formalization' of Selection. (30th January 2012) - Noon, Mike; Healy, Geraldine; Forson, Cynthia; Oikelome, Franklin
Abstract : This paper explores how formalization of employee selection procedures for the purpose of ensuring equality of opportunity can become so extensive that the intended outcome of fairness is undermined. Drawing on empirical evidence from a large media organization, the analysis reveals the detrimental impact of formalization in relation to the recruitment of ethnic minority staff. While the existing literature describes how, during recruitment of employees, the circumvention of formal equality procedures can occur through managerial neglect and manipulation, the analysis in this paper shows that, paradoxically, circumvention can also occur through compliance with procedures. This new category takes three forms (robotic, defensive and malicious) and appears under conditions of excessive formalization – the term hyper‐formalization is coined to describe this. The paper develops new concepts that add to understanding of the limitations of equality and diversity procedures, and brings fresh challenges to some of the liberal assumptions about the efficacy and desirability of formalization for achieving fairness.